Valuasi Ekonomi: Travel Cost dan Willingness To Pay Ekowisata Taman Nasional Komodo - Haggy Bakti Batubara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The status of the Komodo National Park area was designated as a conservation area or World Heritage Site and a Man and Biosphere Reserve by UNESCO in 1988, so the zoning of the Komodo National Park area is also regulated by the government in Article 32 of Law of the Republic of Indonesia No. 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems. This zoning is carried out to protect areas that are vulnerable and have a high environmental valuation. The Tourism Use Zone is the only zone that tourists can visit and has the least negative impact on the Komodo dragon population. This zone is restricted for ecotourism purposes and is strictly guarded by the national park authorities. Changes in the management landscape of the Komodo National Park area based on environmental sustainability tourism (ecotourism) in 1995 changed management policies which also changed the socio-economic pattern of the community, from people who previously relied on garden and sea products for their livelihoods to now being based on tourism services and small industries household. This research aims to analyze the assessment of the economic benefits of natural resources through economic valuation in the development of ecotourism in the Komodo National Park and to analyze the role of ecotourism in the economic growth of the Komodo National Park area. This research uses a quantitative canalitis method using secondary data obtained from expert literature, statistical data from the Central Statistics Agency (BPS) and mapping documents of the Konodo National Park. Apart from that, primary data used a questionnaire from Komodo National Park tourists and interviews with the Head of the Komodo National Park Office. This research also shows that there is a positive value in total economic valuation from the sum of (indirect use value/Willingness To Pay and direct use value/Travel Cost) on the economic growth of the Komodo National Park Area. Economic growth in the Komodo National Park area is not only assessed from the benefits of total economic valuation (TEV), but also the assessment of leading sectors (basic and non-basic) in West Manggarai Regency and East Nusa Tenggara Province. The assessment of the leading sectors in this research uses Location Quotients (LQ) analysis. This analysis will look at activity sectors that drive economic growth in the Komodo National Park area.